Incidence of snake bite and corresponding compensation payments in the Kannur district of Kerala, India - Ramesh. ROSHNATH; Edakkepurath KUNHIRAMAN AND Chandera V. RAJAN (The Herpetological Bulletin, 2018)
Data on snake bite cases were collected from a hospital that is the main centre for the diagnosis and treatment of envenomation and poisoning in the Kannur district of Kerala (India), from 2012-2015. Data on financial compensation for snake bite was collected from the Kannur Forest Department in the same period. A total of 770 snake bites were recorded, of which 487 were from Hypnale hypnale (hump-nosed pit-viper), 281 from Daboia russelii (Russell’s viper), and one incidence each of bites by Naja naja (Indian spectacled cobra) and Bungarus caeruleus (common krait). Snake bites were most frequent in summer and during the wet season and most common in individuals aged 40-50 years. Although 770 snake bite cases were recorded in the period, Kannur Forest Department paid snake bite compensation in only 452 cases (58%). This amounted to US$0.63m for snake bite mortality and US$1.081m for morbidity. We suggest that increasing the knowledge and awareness of the general public about venomous snakes could reduce the risk of snake bite.